Brand Betrayal or Market Shift? Disentangling Boycott Motivations from Other Causes of Declining Sales - Putra, Halim Dwi; Aswandi, Aswandi; Gunawan, M. I. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the multifaceted decline in Pizza Hut Indonesia’s sales by distinguishing between consumer boycott motivations and other contributing market forces. A major factor identified is the rise of more affordable alternatives, notably street food vendors, which have attracted cost-conscious consumers and accounted for a significant 30% drop in sales. These vendors offer convenient and budget-friendly meals that align better with evolving consumer spending habits. Despite this, Pizza Hut has shown progress in product enhancement, reflected in a 31% increase in customer satisfaction—driven by menu innovations such as Indonesian-flavored and fusion-style pizzas tailored to diverse local palates. Nevertheless, brand trust has been undermined by health-related perceptions, with 32% of the negative impact attributed to concerns over the nutritional value of offerings. In response, the brand has introduced healthier options, including whole wheat crusts, fresh vegetables, and lean proteins, to regain the confidence of health-conscious customers. Importantly, consumer boycotts have been identified but exert only a minor influence, contributing just 5% to the sales decline. These boycotts stem from issues such as perceived service shortcomings or pricing dissatisfaction, yet have had limited financial repercussions due to counteractive strategies like targeted promotions, loyalty schemes, and improved service quality. Additionally, macroeconomic conditions have imposed a 2% impact, compelling Pizza Hut to adapt pricing strategies during periods of financial constraint, such as offering value deals to sustain customer interest. In conclusion, this study highlights the necessity of differentiating brand-related backlash from broader market shifts.